2001
DOI: 10.1007/s004670100672
|View full text |Cite
|
Sign up to set email alerts
|

Renal hemodynamic effects of L-NAME during postnatal maturation in conscious lambs

Abstract: The purpose of the present study was to investigate the effects of the L-arginine analogue, NG-nitro-L-arginine methyl ester, L-NAME, in modulating renal hemodynamics during postnatal maturation in conscious chronically instrumented lambs. To this end, renal hemodynamic responses to intravenous injection of 10, 20, and 40 mg/kg L-NAME, as well as its inactive enantiomer D-NAME, were measured for 4 h in conscious lambs approximately 1 week (n=10), 3 weeks (n=12), and 6 weeks (n=14) of age. Administration of L-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
42
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 20 publications
8
42
0
Order By: Relevance
“…In previous studies carried out in conscious, chronically instrumented lambs, we provided evidence that some of the physiological effects of NO produced by the constitutive isoforms of NOS are developmentally regulated (30)(31)(32). For example, administration of the L-arginine analog, N G -nitro-L-arginine methyl ester (L-NAME), which competitively inhibits both n-and eNOS isoforms, is associated with an increase in mean arterial pressure (MAP) in 1-and 6-wk-old lambs that is similar in both age groups; the concomitant decrease in heart rate (HR) is, however, greater at 1 than at 6 wk of age (31).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In previous studies carried out in conscious, chronically instrumented lambs, we provided evidence that some of the physiological effects of NO produced by the constitutive isoforms of NOS are developmentally regulated (30)(31)(32). For example, administration of the L-arginine analog, N G -nitro-L-arginine methyl ester (L-NAME), which competitively inhibits both n-and eNOS isoforms, is associated with an increase in mean arterial pressure (MAP) in 1-and 6-wk-old lambs that is similar in both age groups; the concomitant decrease in heart rate (HR) is, however, greater at 1 than at 6 wk of age (31).…”
mentioning
confidence: 90%
“…The role of endogenously produced NO in modulating renal hemodynamics is also greater in lambs aged 1 wk compared with 3-and 6-wk-old lambs (31). Furthermore, the renal distribution of NOS is also developmentally regulated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Solhaug et al were the first to show an enhanced role for NO in the neonate in 1993, when intrarenal infusion of the nonspecific NOS inhibitor l-NAME into porcine caused significantly greater changes in RVR, RBF, and GFR in the newborn, than in the adult (6). This finding by Solhaug et al was confirmed in other animal models (lambs and rabbits) in which nonspecific NOS inhibition increased RVR while decreasing RBF and GFR much more significantly in neonates than in adult kidneys (4,5,8). These early studies demonstrated that the renal hemodynamics of the neonate is much more dependent on NO than that of the adult to maintain normal physiological function; however, the characteristics and exact nature of the enhanced role of NO remain unidentified.…”
Section: Discussionmentioning
confidence: 89%
“…Various studies have shown that nitric oxide (NO) plays a much more pronounced role in the neonate's hemodynamic state, as compared with the adult's, and NO counterbalances the highly activated reninangiotensin system (RAS), protecting the immature kidney from the deleterious effects of adverse perinatal events that lead to vasomotor acute renal failure (2)(3)(4)(5)(6)(7). The immature renal vasculature is highly responsive to intrarenal NO stimulation with acetylcholine and NO inhibition with the nonselective nitric oxide synthase (NOS) inhibitor L-nitro-arginine methyl ester (l-NAME) (8)(9)(10)(11), producing significantly greater increases in RVR and decreases in RBF and GFR in the immature kidney, as compared with the adult. However, because all previous studies in the developing kidney have utilized the nonselective NOS inhibitor l-NAME, it is not known which NOS isoform-endothelial NOS (eNOS) or neuronal NOS (nNOS)-predominately regulates immature renal hemodynamics.…”
mentioning
confidence: 99%